A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Induction of lactadherin mediates the apoptosis of endothelial cells in response to advanced glycation end products and protective effects of grape seed procyanidin B2 and resveratrol - Bao-ying Li; Xiao-li Li; Qian Cai; Hai-qing Gao; Mei Cheng; Jian-hua Zhang; Jun-fu Wang; Fei Yu; Rui-hai Zhou (Apoptosis, 2011)

Diversity, abundance and characterization of ruminal cysteine phytases suggest their important role in phytate degradation - Huoqing Huang; Rui Zhang; Dawei Fu; Jianjie Luo; Zhongyuan Li; Huiying Luo; Pengjun Shi; Peilong Yang; Qiyu Diao; Bin Yao (Environmental Microbiology, 2011)
Summary A novel class of cysteine phytase showing ability to degrade phytate has recently been isolated from rumen bacteria. To expand our knowledge of this enzyme class, a total of 101 distinct cysteine phytase gene fragments were identified from the ruminal genomic DNA of Bore goats and Holstein cows, and most of them shared low identities (